The occurrence and abundance of microplastics in surface water of the midstream and downstream of the Cisadane River, Indonesia. (March 2022) - Sulistyowati, Lilik; Nurhasanah; Riani, Etty; Cordova, Muhammad Reza
Abstract: This study investigates microplastic contamination in the midstream to downstream of the Cisadane River and its confluence with the Java Sea. The abundance ranged between 13.33 and 113.33 particles m −3 in surface water samples. Microplastic abundance in the downstream area was higher than midstream. We discovered 11 microplastic polymer types, with polyethylene, polystyrene, and polypropylene dominating (>70%) the chemical composition study result, which we hypothesized was owing to their ubiquitous use in daily household and industrial activities. Microplastic fragments with a diameter of 500–1000 m predominated in surface water samples. This study identifies possible microplastics pollution hotspots throughout the Cisadane rivers and selects sites that require additional sampling. Runoff from cities and landfills has the potential to have a significant impact on the accumulation and movement of microplastics from the inland to the Cisadane estuarine area. Additional research is necessary to determine how and where these microplastics particles enter rivers. Graphical abstract: Image 1 Highlights: Microplastics in the surface water of Cisadane River were examined for the first time. Microplastic abundance in the downstream area was higher than midstream. Polyethylene, polystyrene, and polypropylene dominating the chemical composition. Two landfills identified as possible microplastics point sources to the river.